HUBUNGAN TINGKAT KECUKUPAN ENERGI DAN PROTEIN DENGAN STATUS GIZI PEKERJA WANITA DI SENTRA INDUSTRI SANDAL, SIDOARJO - Ellyke Ellyke (Fakultas Kesehatan Masyarakat, Universitas Jember, 2007)
One of the phenomena arising from the development process which has been carried out for the last twenty years is the increasing number of working women. The amount of energy and protein consumption in proportion with the kind of job will influence work capacity. This research was to find out the relation between the sufficiency of energy and protein and the nutrition status among working women (shoes and slippers retailers) at the Slippers Industrial Center at Sidoarjo. This research was descriptive, using cross-sectional design. The population were all the working women at the Slippers Industrial Center. The sample were 30 working women with the age range 20-59 years-old who were physically healthy, not pregnant, nor breast feeding and willing to be a sample who were taken by using purposive sampling. The finding of the research shows that the average of the working women’s daily enegy consumption was 1340 calories and the average of the daily protein consumption was 46,5 grams. 33,3% of the working women have the of energy sufficiency less than 70% RDA and 60% have the of protein sufficiency more than 100% RDA. Additionally, 60% of the working women has the normal nutrition status. The statistical test using Spearman Corrrelation shows that there was no relation between nutrition status and the of energy sufficiency (p=0,076) however, there was relation between nutrition status and the of protein sufficiency (p=0,046). Based on the findings of the research, it is suggested that the carbohydrate consumption be increased and the daily food consumption be varied in order to get energy and protein sufficiency. Key words : working women, nutrition status, the sufficiency level of energy and protein